Knowledge About Scabies Among Students At High Institute Of Health Science - Hajjah Branch(YEMEN) - Badr, Abdulnaser; Dr. Ahmad Taufik; Abu Al-Ghaith, Dr. Fuoz (Enhanced Knowledge in Sciences and Technology, 2022)
The purpose of this study was to assess the level of Knowledge about scabies among students at the High Institute of Health Sciences - Hajjah branch,Yemen. A cross-sectional study was conducted at the High Institute of health science - Hajjah branch in Hajjah city among 260 students studying at Health Institute . The data were collected by using self administered structured questionnaire. SPSS software was used for data analysis. Approximately 31.5% of students were classified as having adequate knowledge of Scabies . Most of the students reported that scabies is a communicable disease (90.9%),but only (29.7%) of students reported that a parasite is the causative agent of Scabies. Surprisingly, (12.3 %) students know of appropriate drugs for scabies and (39.3 %) students reported that there’s a vaccination against scabies . Health facilities were the most common sources of the knowledge among them . This study found that there is an association between (study level, departments and residency) and level of knowledge about the scabies disease among students. (p = 0.002, p = 0.013, p = 0.029) respectively. The result showed that the knowledge level was moderate in students and health facilities were the most preferred sources of the knowledge. Thus, interventions for knowledge improvement should be more on students and the community in Hajjah governorate.